EFFICACY OF DIFFERENT TREATMENT MODALITIES ON SPASTICITY MANAGEMENT OF SPINAL CORD INJURY USING H-REFLEX STUDY (Iraqi Journal of Medical Sciences, 2016)
Background: Spasticity is one of the most frequently observed phenomena after a lesion of the upper motor neuron system. Treatment of spasticity should not be aimed at its complete removal but rather at improving function, easing care or alleviating pain.Objective:To evaluate the effectiveness of oral antispasticity drugs, transcutaneous electrical nerve stimulation and physical therapy alone on the management of spinal cord injury spasticity by using the H-reflex.Methods: Fifty nine patients with traumatic spinal cord injury suffering from spasticity divided into 5 groups (positive controls, group I who were subjected to a regular physical therapy program, group II who were taking the oral anti-spasticity drug (Baclofen) and were performing the same previous physical therapy program, group III who were subjected to transcutaneous electrical nerve stimulation therapy and performed the same previous physical therapy program, group IV who were taking the oral anti-spasticity drug (Tizanidine) and were subjected to the same previous physical therapy program and 31 normal volunteers were studied. Electrophysiologic study of H-reflex including H latency, H duration, H-reflex conduction velocity and H max/M max ratio.Results:Highly significant difference was noticed between the pre- and post-treatment assessments in group I and III in H max/M max ratio. Conclusion: Spasticity can be effectively treated but a multidisciplinary approach is required since it is unusual for a single intervention, such as oral medication or physiotherapy alone, to be the only modality needed.Keywords:H-reflex, Spasticity, Spinal cord injury.
Keywords: Hreflex; Spasticity; Spinal cord injury